Modele klas ukrytych dla tablic kontyngencji z brakującymi danymi - Kasprzyk, Iwona (Latent class model for contingency tables with missing data, 2006)
The missing data are common problem in many types of data analysis. The main purpose of this paper is to present latent class models in a view of a log-linear approach. This article demonstrates the latent class model for complete data and three basic types of mechanisms: missing completely at random (MCAR), missing at random (MAR) and not missing at random (NMAR). This article presents a result of research, which was made among mobile phone users.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 475-482